Stink bugs (Hemiptera: Heteroptera: Pentatomidae) of Colombia: An annotated checklist of species - Castro Huertas, Valentina (2022)
A checklist of 5 subfamilies, 108 genera, and 246 species of stinks bugs (Hemiptera, Pentatomidae) from Colombia is provided. Three genera [Andrallus Bergroth, Placocoris Mayr, and Pseudobebaeus Distant], and eight species [Arocera spectabilis (Drury), Andrallus spinidens (Fabricius), Banasa excavata Thomas, Banasa saileri Thomas, Banasa varians Stål, Chinavia scutellata (Distant), Pelidnocoris haglundi Ruckes, and Pseudobebaeus truncatus (Fallou)] are recorded for the first time from Colombia. Images of dorsal external habitus for all genera that occur in Colombia are offered. This is the first time a comprehensive list of the stink bugs from Colombia is presented, providing a baseline to develop further studies in this group of true bugs.